A Workplace Dignity Perspective on Resilience: Moving Beyond Individualized Instrumentalization to Dignified Resilience. Issue 4 (November 2020) - Bal, Matthijs; Kordowicz, Maria; Brookes, Andy
The Problem: Resilience discourses in society and the contemporary workplace tend to emphasize the self-directed nature of resilience and the imposed demand for resilience for survival in the contemporary labor market. The Solution: In this article, the anchoring point of resilience is analyzed when conceptualized within a neoliberal and self-directed ideology. Subsequently, it offers an alternative anchoring point through a dignity-perspective on resilience, through which the term is reinterpreted in a new meaning. The Stakeholders: This article offers scholars, practitioners and policy-makers insights into how resilience can be conceptualized and used in practice. Analyzing resilience through a dignity lens provides new meanings and more effective uses of resilience in society and the contemporary workplaces.